A hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles and its preparation method

By introducing nano-gold particle buried layer and dual-channel input structure into the MZI optical switching chip, switching control of the fundamental mode and advanced mode is realized, solving the problem of unbalanced response speed and power consumption of existing optical switching devices, and achieving efficient and fast mode optical switching functions.

CN118884764BActive Publication Date: 2025-03-25BAOTOU XINXINWEI TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410625570.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-03-25
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

The existing MZI type optical switching devices cannot achieve on/off control of high-order modes, which limits their development in mode-division multiplexing systems. At the same time, electro-optical switches are easily affected by losses, thermal switches are slow to respond, and power consumption is unbalanced.

Method used

A hybrid integrated M-Z-type mode all-optical switching chip using nano-gold particles buried is used to achieve switching control of the fundamental mode and advanced mode through the dual-channel input MZI-type optical waveguide structure and nano-gold particle buried layer, reducing power consumption and improving response speed.

Benefits of technology

Switching control in different modes is realized, switching response rate is improved, power consumption is reduced, and it is easy to integrate with optical chip systems, solving the shortcomings of traditional optical switching devices in response speed and power consumption balance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118884764B_ABST
    Figure CN118884764B_ABST
Patent Text Reader

Abstract

The present invention provides a hybrid integrated M-Z mode all-optical switch chip buried with nano-gold particles, comprising a substrate layer, an MZI waveguide is arranged on the substrate layer, an upper cladding layer covering the MZI waveguide and having a lower refractive index than the MZI waveguide is grown outside the MZI waveguide; the MZI waveguide is a dual-channel input MZI optical waveguide structure, a nano-gold particle buried layer for phase modulation is arranged in the middle of the dual-channel input MZI optical waveguide structure, and the nano-gold particle buried layer is formed by nano-gold particles dispersed in a polymer. The present invention reduces the power consumption of optical switch devices and achieves higher light excitation efficiency and realizes the regulation of optical switches through the nano-gold particle buried layer structure and the photothermal effect of the nano-gold particles; compared with the traditional thermal optical switch, the electrode structure is omitted, the switch response speed is faster, and it is easy to integrate with the optical chip system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical waveguide mode optical switches, and in particular to a hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles and a preparation method thereof. Background Art

[0002] Common optical switches include mechanical optical switches, liquid crystal optical switches, bubble optical switches and waveguide optical switches. Compared with other types of optical switches, waveguide optical switches are widely used due to their compact structure, fast response speed, good stability, and easy integration. At present, according to the structure of waveguide optical switch devices, there are mainly X-junction type and MZI type (also known as MZ type) optical switches. Compared with the X-junction type, the MZI type optical switch device has lower power consumption and faster response speed. It is the most basic and easy-to-implement interference type optical waveguide structure in optical switch devices. The MZI type optical switch is usually composed of a straight waveguide with single-channel / dual-channel input or output, a Y-branch waveguide and a parallel interference waveguide. However, due to the limitations of the device structure, the optical switch with MZI structure can usually only realize the switch regulation of the fundamental mode, and cannot realize the on / off control function of the higher-order mode, which limits the further development of the MZI type optical switch in the mode division multiplexing system.

[0003] Waveguide optical switches mainly include electro-optic switches and thermo-optic switches. Due to material limitations, electro-optic switches are easily affected by free carrier absorption, which increases device losses. In addition, they are also affected by the elasto-optic effect, which limits the development of electro-optic switch integration. In thermo-optic switches, polymer materials have a large thermo-optic coefficient, so polymer optical switches have the advantage of lower power consumption, but the device response speed is slow. Inorganic materials have high thermal conductivity, so inorganic thermo-optic switches have a fast response speed, but the disadvantage is that the device consumes more power. In order to balance the limitations of the two chips, organic / inorganic hybrid integrated thermo-optic switches have become a research focus in recent years. In addition, very high-performance materials such as graphene and phase change materials have been integrated to further improve the performance of thermo-optic switches. For example, the application publication number is CN 111175898 A's Chinese invention patent discloses a vertically integrated silicon dioxide-polymer three-dimensional MZI waveguide thermo-optical switch prepared by three-dimensional integration technology and its preparation method, which comprises depositing and growing a layer of germanium-doped high-refractive-index SiO2 layer on a substrate; then preparing a waveguide structure with germanium-doped SiO2 as the core layer; using the SiO2 layer as the upper cladding of the lower waveguide and the lower cladding of the upper waveguide; then preparing a second mask layer, plasma etching the SiO2 layer to obtain a groove; spin coating a PMMA layer, and obtaining an inverted ridge-shaped waveguide core layer after spin coating; spin coating an upper cladding layer, and preparing Metal electrode; the switch power consumption of this invention is 8mW, the rise time is 190μs, and the fall time is 130μs. Although this invention solves the problems of power consumption and response rate to a certain extent, its electrode heating efficiency is low, the response speed is slow, and the applicable mode is single, making it difficult to achieve switch regulation in different modes. The switch response rate is still low, and both electro-optical and thermo-optical switches require electro-optical or thermo-optical conversion, which increases the additional loss caused by the energy conversion process, which is not conducive to the optical switch chip in the all-optical communication network for mode division multiplexing system.

[0004] With the continuous development of optical information networks and the increasing demand for information transmission rates, optical switch chips not only have high-speed requirements for information transmission, but also need to allocate optical network resources efficiently and quickly to build a flexible mode division multiplexing system. That is, it is necessary to realize the conversion of base mode and advanced mode and the switching function of different channels, which can effectively reduce the congestion of communication networks and improve the information processing rate. Therefore, the development of a high-speed, efficient, reliable and flexible mode optical switch chip has important research significance and application prospects. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and provide a hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles. The switch chip can realize switch regulation of different modes and improve the switch response rate. Another purpose of the present invention is to provide a preparation method of the high-speed, efficient, reliable and flexible mode optical switch chip.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A nano-gold particle buried hybrid integrated MZ mode all-optical switch chip comprises a substrate layer, an MZI waveguide is arranged on the substrate layer, an upper cladding layer covering the MZI waveguide and having a lower refractive index than the MZI waveguide is grown outside the MZI waveguide; the MZI waveguide is a dual-channel input MZI optical waveguide structure, a nano-gold particle buried layer for phase modulation is arranged in the middle of the dual-channel input MZI optical waveguide structure, and the nano-gold particle buried layer is formed by dispersing nano-gold particles in a polymer.

[0008] The present invention reduces the power consumption of optical switch devices and achieves higher light excitation efficiency through the nano-gold particle buried layer structure and the photothermal effect of the nano-gold particles, thereby realizing the regulation of optical switches. Compared with traditional thermal-optical switches, the electrode structure is omitted, the switch response speed is faster, and it is easy to integrate with optical chip systems.

[0009] Furthermore, the dual-channel input MZI type optical waveguide structure includes a first parallel input straight waveguide and a second input straight waveguide, the other ends of the first input straight waveguide and the second input straight waveguide are respectively connected to a first curved waveguide and a second curved waveguide, and the other ends of the first curved waveguide and the second curved waveguide are inwardly connected to a third straight waveguide; the other end of the third straight waveguide is outwardly connected to a third curved waveguide and a fourth curved waveguide, respectively, the other ends of the third curved waveguide and the fourth curved waveguide are respectively connected to a first coupled arm waveguide and a second coupled arm waveguide, the other ends of the first coupled arm waveguide and the second coupled arm waveguide are respectively connected to a fifth curved waveguide and a sixth curved waveguide, the other ends of the fifth curved waveguide and the sixth curved waveguide are inwardly connected to a fourth output straight waveguide, the first input straight waveguide and the second input straight waveguide are parallel, and the first coupled arm waveguide and the second coupled arm waveguide are parallel; the nanogold particle buried layer is arranged in the middle of the first coupled arm waveguide.

[0010] Furthermore, the nano-gold particles in the nano-gold particle embedding layer have a light excitation wavelength of 0.45 to 0.65 nm, a particle radius of 2 to 80 nm, a particle spacing of 0.5 to 3.5 μm, and a particle doping concentration of 0.0025% to 0.5%.

[0011] Preferably, the radius of the gold nanoparticles is 10-80 nm.

[0012] Preferably, the radius of the gold nanoparticles is 2-15 nm.

[0013] Preferably, the radius of the gold nanoparticles is 2-5 nm or 10-15 nm.

[0014] Furthermore, the MZI waveguide comprises a first polymer core layer and a second polymer core layer, and the materials of the first polymer core layer and the second polymer core layer are selected from EPO Core, SU-8 2002 or SU-8 2005.

[0015] Furthermore, the material of the upper cladding layer is selected from polymethyl methacrylate, EPO Clad, polyester or polyimide.

[0016] Furthermore, the nano-gold particle embedding layer is formed by dispersing nano-gold particles in a polymer, and the polymer is selected from polymethyl methacrylate, EPO Core, SU-8 2002 or SU-8 2005.

[0017] Furthermore, the thickness of the substrate layer is 0.5-1 mm, the thickness of the first polymer core layer is 1-10 μm, the thickness of the nano-gold particle burying layer is 0.1-2 μm, the thickness of the second polymer core layer is 1-10 μm, and the thickness of the upper cladding layer is 2-15 μm.

[0018] Preferably, the first polymer core layer thickness and the second polymer core layer thickness are the same.

[0019] Preferably, the polymer core layer has a thickness of 2 to 6 μm.

[0020] Furthermore, the first bend waveguide, the second bend waveguide, the third bend waveguide, the fourth bend waveguide, the fifth bend waveguide and the sixth bend waveguide are S-bend waveguides with the same structure and size, and the S-bend waveguide uses a cosine-type function waveguide: y=(1-cosπx / a)·d, wherein x is the coordinate of the light transmission direction in the waveguide, y is the coordinate in the direction perpendicular to the waveguide, a is the projection of the S-bend waveguide in the top-down direction of the waveguide parallel to the light transmission direction, and d is the projection of the S-bend waveguide in the top-down direction of the waveguide perpendicular to the light transmission direction.

[0021] Furthermore, the lengths l1, l2 and l6 of the first input straight waveguide, the second input straight waveguide and the output straight waveguide are 0.5-1.5 cm, the horizontal lengths a1, a2 and a3 of the first curved waveguide, the second curved waveguide, the third curved waveguide, the fourth curved waveguide, the fifth curved waveguide and the sixth curved waveguide are 0.1-1 cm, the vertical distances d1, d2, d3, d4, d5 and d6 of the first curved waveguide, the second curved waveguide, the third curved waveguide, the fourth curved waveguide, the fifth curved waveguide and the sixth curved waveguide are 0.5-50 μm, the length l3 of the third straight waveguide connected to the first curved waveguide and the second curved waveguide is 0.2-1.5 cm, the lengths l4 and l5 of the first coupled arm waveguide and the second coupled arm waveguide are 0.5-1.5 cm, the length l7 of the nanogold particle buried layer is 0.2-1 cm, and the width w is 1-10 μm.

[0022] The present invention also provides a method for preparing the hybrid integrated MZ mode all-optical switch chip buried with the nano-gold particles, comprising the following steps:

[0023] S1. Preparation of the first polymer core layer

[0024] Spin coating the first layer of polymer material on the surface of the clean and dry substrate layer, then placing it on a hot plate for pre-heating, after cooling, contacting the first MZI type photomask with the first layer of polymer material, then performing ultraviolet exposure, post-baking treatment, cooling and developing, removing the area outside the first MZI type photomask, and then performing hardening treatment to obtain an MZI type first polymer core layer sample;

[0025] S2. Preparation of gold nanoparticle buried layer

[0026] The nano-gold powder is mixed into the polymer material and uniformly mixed to form a composite material, and then the composite material is spin-coated on the MZI type first polymer core layer sample in step S1, and heated and fixed to obtain a sample containing a nano-gold particle buried layer;

[0027] S3. Preparation of the Second Polymer Core Layer

[0028] Spin coating the second layer of polymer material on the surface of the sample containing the nano-gold particle embedding layer in step S2, pre-heating and cooling, using an ultraviolet photoresist mask and a plate alignment technology to contact the second MZI type photoresist plate matching the first polymer core layer with the sample surface, and accurately copy the pattern on the second polymer core layer on the first polymer core layer; then ultraviolet exposure, post-baking treatment, cooling and development, removing the area outside the second MZI type photoresist plate, and then hardening treatment to obtain an MZI type second polymer core layer sample;

[0029] S4. Preparation of optical waveguide upper cladding

[0030] The spin coating process is adopted to spin-coat the polymer as the upper cladding material on the second polymer core layer sample of the MZI type, heat and solidify it, and cool it to obtain the upper cladding structure, thereby obtaining a hybrid integrated MZ type mode all-optical switch chip buried with nano-gold particles.

[0031] The preparation process of the present invention is simpler. The thickness of the polymer core layer is controlled by a simple process. Compared with the traditional MZI structure that can only achieve the regulation of optical power and phase, the hybrid integrated MZI structure provided by the present invention can respectively realize the switching functions of the fundamental mode and the first-order mode, breaking through the limitations of the traditional MZI structure.

[0032] Furthermore, the substrate layer in step S1 is a silicon-based silicon dioxide substrate.

[0033] Furthermore, when the first layer of polymer material is spin-coated on the surface of the substrate layer in step S1, the silicon-based silica substrate needs to be cleaned, and the method used is: immersing the silicon-based silica substrate in an acetone solution, ultrasonically cleaning it with an ultrasonic machine for 10 to 15 minutes, and then gently and repeatedly scrubbing the surface of the silicon-based silica substrate with cotton balls soaked in acetone and ethanol solutions, respectively, and then rinsing it with deionized water 2 to 3 times, blowing the moisture on the surface of the silicon-based silica substrate with nitrogen, and then placing it in an oven and baking it at a temperature of 100 to 120° C. for 1 to 2 hours to remove moisture from the surface of the silicon-based silica substrate to obtain a dry and clean substrate layer.

[0034] Furthermore, the spin coating in step S1 adopts a spin coating process, and the method is: spin coating the first layer of polymer material on the surface of the substrate layer, the rotation speed is 1000-7000 r / min, the pre-spinning time is 10-40 s, and the spin coating time is 20-100 s.

[0035] Furthermore, the pre-baking conditions in step S1 are: heating at 60-100° C. for 10-20 min, and then heating at 90-120° C. for 20-40 min.

[0036] Furthermore, in step S1, the area outside the MZI photomask is removed by using an ultraviolet photoresist masking technique, wherein the first MZI photomask is contacted with the first layer of polymer material, and then ultraviolet exposure is performed, the exposure time is 4 to 30 seconds, and the exposure intensity is 20 to 200 mW / cm 2 , the exposure wavelength is 360-370nm; after UV exposure, post-baking treatment is carried out: heating on a hot plate at 60-100℃ for 10-20min, heating at 75-120℃ for 20-40min, and then turning off the hot plate for cooling; after the sample is cooled to room temperature, the sample is placed in a developer matching the photoresist, and the wet etching time is 20-40s to remove the area outside the MZI photoresist.

[0037] Furthermore, after removing the area outside the MZI type photomask in step S1, it is necessary to rinse off the developer on the surface of the sample with an isopropyl alcohol solution, and then repeatedly rinse the sample with deionized water 2 to 3 times to remove the residual reagent, and then blow dry.

[0038] Furthermore, the hardening treatment in step S1 is performed by heating the sample at 80-150° C. for 30-40 minutes on a hot plate.

[0039] Furthermore, the preparation method of the composite material described in step S2 is as follows: 0.1-1g of nano-gold powder is added to 40-60mL of polymer material to form a composite material, stirred at a uniform speed for 8-12h on a stirring table at a temperature of 30-40°C, and then ultrasonicated with an ultrasonic machine at high frequency for 12-24h; then, 0.05-10mL of the above mixed liquid is respectively added to 5mL of the polymer material again, stirred at a uniform speed for 8-12h on a stirring table at a temperature of 30-40°C, and then ultrasonicated with an ultrasonic machine at high frequency for 12-24h to obtain a composite material.

[0040] Furthermore, the heating curing in step S2 is heating at 80-150° C. for 40-100 min.

[0041] Furthermore, the spin coating in step S3 adopts a spin coating process, and the method is: spin coating the second layer of polymer material on the surface of the sample containing the nano-gold particle embedding layer, the rotation speed is 1000-7000r / min, the pre-gelling time is 10-40s, and the spin coating time is 20-100s.

[0042] Furthermore, the pre-baking conditions in step S3 are: heating at 60-100° C. for 10-20 min, and then heating at 90-120° C. for 20-40 min.

[0043] Furthermore, in step S3, the area outside the second MZI type photomask is removed, and an ultraviolet photoresist mask technology is used, wherein the second MZI type photomask matching the first polymer core layer is closely contacted with the surface of the sample, and the pattern of the second polymer core layer is accurately copied on the first polymer core layer according to the registration pattern on the second MZI type photomask; and then ultraviolet exposure is performed, and the exposure time is 4 to 30 seconds, and the exposure intensity is 20 to 200 mW / cm 2 , the exposure wavelength is 360-370nm; after ultraviolet exposure, the sample is post-baked: heated on a hot plate at 60-100°C for 10-20min, heated at 75-120°C for 20-40min, then the hot plate is turned off and cooled to room temperature, and the sample is placed in a developer matching the photoresist. The wet etching time is 20-40s to remove the area outside the second MZI type photoresist.

[0044] Furthermore, the hardening treatment in step S3 is performed by heating the sample at 80-150° C. for 30-40 minutes on a hot plate.

[0045] Furthermore, the spin coating process in step S4 has a spin coating speed of 3000 to 5000 r / min and a spin coating time of 30 to 60 s.

[0046] Furthermore, the heating curing in step S4 is to place the sample on a hot plate and heat it for 20 to 90 minutes at a heating temperature of 90 to 140°C.

[0047] Furthermore, the upper cladding layer can completely cover the first polymer core layer, the nano-gold particle embedding layer and the second polymer core layer, and the thickness of the upper cladding layer is 2 to 10 μm.

[0048] Furthermore, after the preparation of the upper cladding layer of the optical waveguide in step S4 is completed, the end faces need to be cleaved. The cleaved end faces are cut along a direction perpendicular to the light transmission direction at the input end and the output end of the optical waveguide to obtain neatly cut optical waveguide end faces.

[0049] Preferably, the substrate layer is a silicon-based silicon dioxide substrate or a layer of EPO copolymer or PMMA polymer layer is grown on a silicon-based silicon dioxide substrate.

[0050] Preferably, the substrate layer is a silicon-based silicon dioxide substrate, and the silicon-based silicon dioxide substrate comprises a silicon substrate layer and a silicon dioxide layer epitaxially grown on the upper portion thereof.

[0051] The beneficial effects of the present invention are as follows:

[0052] (1) The present invention utilizes a nano-gold buried structure to achieve the regulation of optical switches. Compared with traditional thermo-optical switches, the electrode structure is omitted, the switch response speed is faster, the preparation process is simpler, and it is easy to integrate with optical chip systems.

[0053] (2) The strong photothermal effect of gold nanoparticles is utilized to reduce the power consumption of optical switching devices and realize the function of all-optical switching control.

[0054] (3) By adopting a dual-channel end-face input structure, compared with the traditional vertical pumping method, the pumping method of the present invention has higher light excitation efficiency and reduces the power consumption of the device.

[0055] (4) The present invention breaks through the limitations of the traditional MZI structure by simply controlling the thickness of the polymer core layer in the process, and uses the finite element calculation method to analyze the light field distribution and thermal field distribution of the optical switch. The present invention realizes the switching function of the fundamental mode and the first-order mode. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 : Schematic diagram of the MZI type waveguide and size of the hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles of the present invention.

[0057] Figure 2 : Schematic diagram of the structure of the hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles of the present invention.

[0058] Figure 3: The preparation process flow chart of the hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles of the present invention.

[0059] Figure 4 : Figure 1 Cross-sectional view of the hybrid integrated MZ-mode all-optical switch chip at m-m' (a) The buried gold nanolayer is located at the center of the polymer core layer (E m 12 mode all-optical switch, where m = x or y, x represents TE polarization mode; y represents TM polarization mode); (b) The buried gold nanolayer is close to the top of the polymer core layer (E m 11 optical switch).

[0060] Figure 5 : The light field mode distribution diagram of the optical switch chip of Comparative Example 1-2 when there is no nano-gold particle burying layer (a) corresponds to the attached Figure 4 E in structure m 11 Mode all-optical switch (b) corresponds to the attached Figure 4 E in structure m 12 Mode full optical switch.

[0061] Figure 6 : The light field distribution diagram of the hybrid integrated MZ mode all-optical switch chip with a buried structure of nano-gold particles (a) corresponds to the attached Figure 4 E in structure m 12 Mode all-optical switch (b) corresponds to the attached Figure 4 E in structure m 11 Mode full optical switch.

[0062] Figure 7 : Attached Figure 4 (a) Thermal field distribution of the mode all-optical switch after light excitation.

[0063] Figure 8 : Attached Figure 4 (b) Thermal field distribution of the mode all-optical switch after light excitation.

[0064] Fig. 9 :(a)E m 12 Response time curve of mode all-optical switch and (b) E m 11 Response time curve of mode all-optical switch;

[0065] Fig.10: The relationship between the loss of the mode all-optical switch and the thickness of the polymer core layer (the radius of the nano-gold particles are: 2nm, 5nm, 10nm, and 15nm respectively).

[0066] Fig.11 : The relationship curve between power consumption and phase of the mode all-optical switch.

[0067] The meanings of the markings in the figure are as follows: 1 is the first input straight waveguide; 2 is the second input straight waveguide, 3 is the first curved waveguide; 4 is the second curved waveguide; 5 is the third straight waveguide; 6 is the third curved waveguide; 7 is the fourth curved waveguide, 8 is the first coupled arm waveguide; 9 is the second coupled arm waveguide; 10 is the fifth curved waveguide; 11 is the sixth curved waveguide; 12 is the fourth output straight waveguide; 20 is the substrate layer; 21 is the silicon substrate layer; 22 is the silicon dioxide layer; 23 is the MZI type waveguide; 24 is the nano-gold particle buried layer; 25 is the second polymer core layer; 251 is the second layer of polymer material; 26 is the upper cladding layer; 27 is the first polymer core layer; 271 is the first layer of polymer material; 100 is the first MZI type photolithography plate; 200 is the second MZI type photolithography plate; l1 represents the length of the first input straight waveguide; l2 represents the length of the second input straight waveguide; l3 represents the length of the third straight waveguide The length of the waveguide; l4 represents the length of the first coupling arm waveguide; l5 represents the length of the second coupling arm waveguide; l6 represents the length of the fourth output straight waveguide; l7 represents the length of the nano-gold particle buried layer; a1 represents the horizontal length of the first curved waveguide and the second curved waveguide; a2 represents the horizontal length of the third curved waveguide and the fourth curved waveguide; a3 represents the horizontal length of the fifth curved waveguide and the sixth curved waveguide; d1 represents the vertical distance between the first curved waveguide and the horizontal axis of symmetry; d2 represents the vertical distance between the second curved waveguide and the horizontal axis of symmetry; d3 represents the vertical distance between the third curved waveguide and the horizontal axis of symmetry; d4 represents the vertical distance between the fourth curved waveguide and the horizontal axis of symmetry; d5 represents the vertical distance between the fifth curved waveguide and the horizontal axis of symmetry; d6 represents the vertical distance between the sixth curved waveguide and the horizontal axis of symmetry; w is the width of the nano-gold particle buried layer. DETAILED DESCRIPTION

[0068] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0069] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the drawings, it is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as limitations on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0070] Example 1

[0071] As the instruction manual Figure 1 and Figure 2 As shown, a hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles comprises a substrate layer 20, on which an MZI waveguide 23 is arranged, and an upper cladding layer 26 covering the MZI waveguide 23 and having a lower refractive index than the MZI waveguide 23 is grown outside the MZI waveguide 23; the MZI waveguide 23 is a dual-channel input MZI optical waveguide structure, and a nano-gold particle buried layer 24 for phase modulation is arranged in the middle of the dual-channel input MZI optical waveguide structure, and the nano-gold particle buried layer 24 is formed by nano-gold particles dispersed in a polymer.

[0072] The dual-channel input MZI type optical waveguide structure includes a first parallel input straight waveguide 1 and a second parallel input waveguide 2. The other ends of the first input straight waveguide 1 and the second input straight waveguide 2 are respectively connected to a first curved waveguide 3 and a second curved waveguide 4. The other ends of the first curved waveguide 3 and the second curved waveguide 4 are inwardly connected to a third straight waveguide 5; the other end of the third straight waveguide 5 is outwardly connected to a third curved waveguide 6 and a fourth curved waveguide 7 respectively. The other ends of the third curved waveguide 6 and the fourth curved waveguide 7 are respectively connected to a first coupling arm waveguide 8 and a second coupling arm waveguide 9. The other ends of the first coupling arm waveguide 8 and the second coupling arm waveguide 9 are respectively connected to a fifth curved waveguide 10 and a sixth curved waveguide 11. The other ends of the fifth curved waveguide 10 and the sixth curved waveguide 11 are inwardly connected to a fourth output straight waveguide 12. The first input straight waveguide 1 and the second input straight waveguide 2 are parallel. The first coupling arm waveguide 8 and the second coupling arm waveguide 9 are parallel. The nano-gold particle buried layer 24 is arranged in the middle of the first coupling arm waveguide 8. The first bend waveguide 3, the second bend waveguide 4, the third bend waveguide 6, the fourth bend waveguide 7, the fifth bend waveguide 10 and the sixth bend waveguide 11 are S-bend waveguides with the same structure and size. The S-bend waveguide uses a cosine-type function waveguide: y=(1-cosπx / a)·d, wherein x is the coordinate of the light transmission direction in the waveguide, y is the coordinate in the direction perpendicular to the waveguide, a is the projection of the S-bend waveguide in the direction parallel to the light transmission direction in the waveguide's top-down direction, and d is the projection of the S-bend waveguide in the direction perpendicular to the light transmission direction in the waveguide's top-down direction.

[0073] As an optional solution, the MZI type waveguide 23 includes a first polymer core layer 27 and a second polymer core layer 25, and the materials of the first polymer core layer 27 and the second polymer core layer 25 are selected from EPO Core, SU-8 2002 or SU-8 2005. As an optional solution, the material of the upper cladding layer 26 is selected from polymethyl methacrylate, EPO Clad, polyester or polyimide. As an optional solution, the nano-gold particle buried layer 24 is formed by nano-gold particles dispersed in a polymer, and the polymer is selected from polymethyl methacrylate, EPO Core, SU-8 2002 or SU-8 2005.

[0074] Preferably, in this embodiment, the material of the first polymer core layer 27 and the second polymer core layer 25 is SU-8 2005; the material of the upper cladding layer 26 is polymethyl methacrylate polymer; in this embodiment, the nano-gold particles are dispersed in the polymer SU-8 2005.

[0075] As an optional solution, the substrate layer 20 is a silicon-based silicon dioxide substrate or a layer of EPO copolymer or PMMA polymer layer is grown on the silicon-based silicon dioxide substrate. Preferably, in this embodiment, the substrate layer 20 is a silicon-based silicon dioxide substrate, and the silicon-based silicon dioxide substrate includes a silicon substrate layer 21 and a silicon dioxide layer 22 epitaxially grown on the upper portion thereof.

[0076] As an optional solution, the thickness of the substrate layer 20 is 0.5-1 mm, the thickness of the first polymer core layer 27 is 1-10 μm, the thickness of the nanogold particle burying layer 24 is 0.1-2 μm, the thickness of the second polymer core layer 25 is 1-10 μm, and the thickness of the upper cladding layer 26 is 2-15 μm.

[0077] Preferably, in this embodiment, the thickness of the substrate layer 20 is 0.8 mm, the thickness of the first polymer core layer 27 is 2 μm, the thickness of the nano-gold particle burying layer 24 is 0.2 μm, the thickness of the second polymer core layer 25 is 2 μm, and the thickness of the upper cladding layer 26 is 8 μm.

[0078] As an optional solution, the lengths l1, l2 and l6 of the first input straight waveguide 1, the second input straight waveguide 2 and the output straight waveguide 12 are 0.5-1.5 cm, the horizontal lengths a1, a2 and a3 of the first curved waveguide 3, the second curved waveguide 4, the third curved waveguide 6, the fourth curved waveguide 7, the fifth curved waveguide 10 and the sixth curved waveguide 11 are 0.1-1 cm, and the first curved waveguide 3, the second curved waveguide 4, the third curved waveguide 6, the fourth curved waveguide 7, the fifth curved waveguide 10 and the sixth curved waveguide 11 are 0.1-1 cm. The vertical distances d1, d2, d3, d4, d5 and d6 between the curved waveguide 10 and the sixth curved waveguide 11 are 0.5 to 50 μm, the length l3 of the third straight waveguide 5 connected to the first curved waveguide 3 and the second curved waveguide 4 is 0.2 to 1.5 cm, the lengths l4 and l5 of the first coupled arm waveguide 8 and the second coupled arm waveguide 9 are 0.5 to 1.5 cm, the length l7 of the nano-gold particle buried layer 24 is 0.2 to 1 cm, and the width w is 1 to 10 μm. Preferably, in this embodiment, l1, l2 and l6 are 1.0 cm, a1, a2 and a3 are 0.3 cm, d1, d2, d3, d4, d5 and d6 are 15 μm, l3 is 0.5 cm, l4 and l5 are 1.0 cm, l7 is 0.5 cm, and the width w is 4 μm.

[0079] Example 2

[0080] As the instruction manual Figure 3 As shown, the method for preparing the hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles described in Example 1 comprises the following steps:

[0081] S1. Preparation of the first polymer core layer

[0082] (1) The substrate layer 20 is a silicon-based silicon dioxide substrate. The silicon-based silicon dioxide substrate is cleaned by soaking the silicon-based silicon dioxide substrate in an acetone solution and ultrasonically cleaning it for 10 to 15 minutes using an ultrasonic machine. In this embodiment, the ultrasonic cleaning is performed for 10 minutes. Then, the surface of the silicon-based silicon dioxide substrate is gently and repeatedly scrubbed with cotton balls soaked in acetone and ethanol solutions, respectively. Then, the surface of the silicon-based silicon dioxide substrate is rinsed with deionized water for 2 to 3 times. The moisture on the surface of the silicon-based silicon dioxide substrate is dried with nitrogen. Then, the substrate is placed in an oven and baked at 100 to 120° C. for 1 to 2 hours. In this embodiment, the substrate is baked at 120° C. for 2 hours to remove moisture from the surface of the silicon-based silicon dioxide substrate and obtain a dry and clean substrate layer 20.

[0083] (2) Spin coating the first layer of polymer material 271 on the clean and dry surface of the substrate layer 20, the polymer material is SU-82005, and then placing it on a hot plate for pre-heating. After cooling, the first MZI type photomask 100 is brought into contact with the first layer of polymer material 271, and then ultraviolet exposure, post-baking treatment, cooling and development are performed to remove the area outside the first MZI type photomask 100, and then hardening treatment is performed to obtain a MZI type first polymer core layer 27 sample;

[0084] As an optional solution, the spin coating in step S1 adopts a spin coating process, and the method is: spin coating the first layer of polymer material 271 on the surface of the substrate layer 20, the rotation speed is 1000-7000 r / min, the pre-spinning time is 10-40s, and the spin coating time is 20-100s. Preferably, the rotation speed of the glue machine in this embodiment is 5000 r / min, the pre-spinning time is 20 seconds, and the spin coating time is 20 seconds.

[0085] As an optional solution, the pre-baking conditions in step S1 are: heating at 60-100°C for 10-20 minutes, and then heating at 90-120°C for 20-40 minutes. Preferably, the pre-baking conditions in this embodiment are: heating at 60°C for 10 minutes, and then heating at 90°C for 20 minutes.

[0086] As an optional solution, the area outside the first MZI type photomask 100 is removed in step S1 by using an ultraviolet photoresist mask technology, and the method is: the first MZI type photomask 100 is contacted with the first layer of polymer material 271, and then ultraviolet exposure is performed, the exposure time is 4 to 30 seconds, and the exposure intensity is 20 to 200 mW / cm 2 , the exposure wavelength is 360-370nm; preferably, the exposure time of this embodiment is 5 seconds, and the exposure intensity is 45mW / cm 2, the exposure wavelength is 367nm; after ultraviolet exposure, post-baking treatment is performed: heating on a hot plate at 60-100℃ for 10-20min, heating at 75-120℃ for 20-40min, and then closing the hot plate for cooling; preferably, in this embodiment, the sample is heated on a hot plate at 60℃ for 10min and 95℃ for 30min after ultraviolet exposure; after the sample is cooled to room temperature, the sample is placed in a developer matching the photoresist, and the wet etching time is 20-40s. Preferably, the wet etching time in this embodiment is 20s, and the area outside the first MZI photoresist 100 is removed. The MZI type first polymer core layer 27 structure is obtained, and then the developer on the surface of the sample is washed off with an isopropyl alcohol solution, and then the sample is repeatedly rinsed with deionized water 2-3 times, and the moisture on the surface of the sample is gently blown dry.

[0087] As an optional solution, the hardening treatment in step S1 is carried out by heating the sample on a hot plate at 80 to

[0088] Heating at 150° C. for 30 to 40 minutes. Preferably, the hardening treatment in this embodiment is to heat the sample at 150° C. for 30 minutes on a hot plate.

[0089] S2. Preparation of gold nanoparticle buried layer

[0090] The nano-gold powder is mixed into the polymer material and uniformly mixed to form a composite material, and then the composite material is spin-coated on the sample of the first polymer core layer 27 of the MZI type in step S1, and heated and fixed to obtain a sample containing the nano-gold particle buried layer 24;

[0091] As an optional scheme, the preparation method of the composite material described in step S2 is: 0.1-1g of nano-gold powder is added to 40-60mL of polymer material to form a composite material, stirred at a uniform speed for 8-12h on a stirring table at a temperature of 30-40°C, and then ultrasonicated with an ultrasonic machine at high frequency for 12-24h; then, 0.05-10mL of the above mixed liquid is respectively added to 5mL of polymer material again, stirred at a uniform speed for 8-12h on a stirring table at a temperature of 30-40°C, and then ultrasonicated with an ultrasonic machine at high frequency for 12-24h to obtain a composite material. Preferably, this embodiment specifically includes adding 0.1g of nano-gold powder to 50mL of polymer material to form a composite material, stirring at a uniform speed for 10h on a stirring table at a temperature of 35°C, and then ultrasonicated with an ultrasonic machine at high frequency for 12h. Then, 0.05, 0.1, 0.3, 0.5, 1, 4, 7 and 10 mL of the mixed liquid were respectively added into 5 mL of the polymer material again, stirred at a constant speed for 12 h on a stirring table at 40°C, and subjected to high-frequency ultrasound for 24 h to obtain nanogold particle / polymer composite materials (the radius of the nanogold particles is 40 nm, and the light excitation wavelength is 532 nm).

[0092] As an optional solution, the light excitation wavelength of the nano-gold particles in the nano-gold particle burying layer 24 is 0.45-0.65 nm, the particle radius is 10-80 nm, the particle spacing is 0.5-3.5 μm, and the particle doping concentration is 0.0025%-0.5%.

[0093] In this embodiment, the nano-gold particles in the nano-gold particle embedding layer 24 preferably have a light excitation wavelength of 530 nm, a particle radius of 40 nm, a particle spacing of 0.5 μm, and a particle doping concentration of 0.48%.

[0094] As an optional solution, the heating and curing in step S2 is heating at 80-150°C for 40-100 minutes. Preferably, in this embodiment, heating at 120°C for 40 minutes obtains the nano-gold particle buried layer 24, the nano-gold particle buried layer 14 has a thickness of 0.2 μm and a length l7 of 0.5 cm. .

[0095] S3. Preparation of the Second Polymer Core Layer

[0096] The second layer of polymer material 251 is spin-coated on the surface of the sample containing the nano-gold particle embedding layer 24 in step S2, and pre-baked before heating. After cooling, a second MZI type photoresist plate 200 matching the first polymer core layer 27 is contacted with the sample surface using an ultraviolet photoresist mask and a plate alignment technology, and the pattern on the second polymer core layer 25 is accurately copied on the first polymer core layer 27; then ultraviolet exposure, post-baking treatment, cooling and development, removing the area outside the second MZI type photoresist plate 200, and then hardening treatment are performed to obtain an MZI type second polymer core layer 25 sample;

[0097] Preferably, the spin coating process and pre-baking in step S3 are the same as those in step S1.

[0098] As an optional solution, the removal of the area outside the second MZI type photomask 200 in step S3 adopts ultraviolet photoresist mask technology, and the method is: the second MZI type photomask 200 matching the first polymer core layer 27 is closely contacted with the surface of the sample, and the pattern of the second polymer core layer 25 is accurately copied on the first polymer core layer 27 according to the registration pattern on the second MZI type photomask 200; then ultraviolet exposure is performed; after ultraviolet exposure, the sample is post-baked, and after cooling to room temperature, the sample is placed in a developer matching the photoresist, and wet etching is used to remove the area outside the second MZI type photomask 200. Preferably, the ultraviolet exposure, post-baking, development wet etching and hardening parameter conditions are the same as those in step S1.

[0099] S4. Preparation of optical waveguide upper cladding

[0100] The upper cladding layer 26 material polymethyl methacrylate polymer is spin-coated on the MZI type second polymer core layer 25 sample by spin coating process, and the upper cladding layer 26 structure is obtained by heating and curing, and cooling to obtain a hybrid integrated MZ type mode all-optical switch chip buried with nano-gold particles.

[0101] As an optional solution, the spin coating process in step S4 has a spin coating speed of 3000-5000 r / min and a spin coating time of 30-60 s. Preferably, in this embodiment, polymethyl methacrylate polymer is spin coated as the upper cladding layer 26 material, and the spin coating speed is 3000 r / min and the spin coating time is 30 s.

[0102] As an optional solution, the heating curing in step S4 is to place the sample on a hot plate and heat it for 20 to 90 minutes at a heating temperature of 90 to 140°C. Preferably, the present embodiment heats the sample on a hot plate for 30 minutes at a heating temperature of 120°C. After the sample is cooled to room temperature, an upper cladding layer 26 structure is obtained, and the thickness of the upper cladding layer 26 is 8 μm.

[0103] As an optional solution, the upper cladding layer 26 can completely cover the first polymer core layer 27, the nano-gold particle burying layer 24 and the second polymer core layer 25. The thickness of the upper cladding layer 26 is 2 to 10 μm. Preferably, the thickness of the upper cladding layer 26 in this embodiment is 8 μm.

[0104] After the preparation of the optical waveguide upper cladding layer 26 is completed in step S4, the end faces need to be cleaved. The cleaved end faces are cut along a direction perpendicular to the light transmission direction at the input end and the output end of the optical waveguide to obtain neatly cut optical waveguide end faces.

[0105] After the end face is dissociated, a hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles is obtained, and the E m 12 Mode all-optical switch, which is convenient for subsequent testing of optical chips. Figure 4 The gold nanoparticles in (a) are buried in the middle of the polymer core layer, that is, the thickness of the first polymer core layer 27 is equal to the thickness of the second polymer core layer 25, which is 2 μm, and the width is 2 μm.

[0106] Example 3

[0107] The difference between Example 3 and Example 2 is that the etching technology is used to control the thickness of the first polymer 27 and the second polymer core layer 25, which can be transformed into E m 11 Mode full optical switch.

[0108] The specific preparation steps differ from those of Example 2 in that:

[0109] The conditions of the spin coating process in the preparation of the first polymer core layer 27 in step S1 are: the rotation speed of the coating machine is 2500 r / min, the pre-coating time is 10 seconds, the spin coating time is 20 seconds. The development time in the wet etching is 25 seconds;

[0110] The conditions of the spin coating process for preparing the second polymer core layer 25 in step S3 are: the rotation speed of the coating machine is 6500 r / min, the pre-coating time is 10 seconds, the spin coating time is 40 seconds, and the development time in the wet etching is 17 seconds;

[0111] Step S3: After the hardening treatment, the reactive ion etching (RIE) method is used, with the second polymer core layer 25 as the etched material and O2 as the process reaction gas, to reduce the thickness of the second polymer core layer 25 and control the buried position of the nano-gold particle burying layer 24. The RF power is 80W, the air pressure is 15Pa, and the etching time is 180s. Finally, on the surface parallel to the light transmission direction, the second polymer core layer 25 has the same structure as the first polymer core layer 27, and the second polymer core layer 25 has a thickness of 1μm and a width of 2μm.

[0112] The remaining steps are the same. After the end face is dissociated, a hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles is obtained, and the E m 11 Mode all-optical switch, which is convenient for subsequent testing of optical chips. Figure 4 The gold nanoparticles in (b) are buried in the polymer core layer near the upper cladding layer 26, that is, the thickness of the first polymer core layer 27 is greater than that of the second polymer core layer 25, which are 2 μm and 1 μm respectively, and the width is 2 μm.

[0113] Comparative Example 1: No Nano-gold Particle Burying Layer

[0114] The preparation method is the same as that of Example 2, except that there is no nano-gold particle embedding layer 24, and the other structures remain unchanged to obtain a switch chip.

[0115] Comparative Example 2: No Nano-gold Particle Burying Layer

[0116] The preparation method is the same as that of Example 3, except that there is no nano-gold particle embedding layer 24, and the other structures remain unchanged to obtain a switch chip.

[0117] Test Example 1 Light Field Pattern, Thermal Field Distribution and Response Time

[0118] 1. Test Method

[0119] The light field mode distribution diagram of comparative example 1-2 and embodiment 2-3 is characterized; the thermal field distribution diagram and response time of embodiment 2-3 are characterized; the characterization is analyzed by finite element analysis method.

[0120] 2. Test results

[0121] The light field pattern distribution results are as follows: Figure 5 and Figure 6 As shown by Figure 5 and Figure 6 It can be seen that when there is no nano-gold particle buried layer 24, according to Figure 5 The optical field mode distribution diagram of the optical switch chip shows that the modified waveguide structure has a significant effect on E m 11 Mode E m 12 The mode is well confined. Since gold nanoparticles absorb the light field in the waveguide, Figure 6 When the nano-gold particles are buried in the structure, the mode all-optical switch is m 12 Mode and E m 11 The light limitation of the mode is good.

[0122] The thermal field distribution results are as follows: Figure 7 and Figure 8 As shown by Figure 7 and Figure 8 It can be seen that according to the principle of photothermal effect, when the nanogold particles are excited by light, they will generate heat. Therefore, the thermal field distribution of the device was characterized. It can be observed from the figure that when the nanogold particles are in the middle, the highest temperature is 297K, and when the nanogold particles are close to the top of the polymer core layer, the highest temperature is 296K. The photothermal conversion efficiency is higher when the nanogold particles are in the middle.

[0123] The response time results are as follows Fig. 9 (a) and 9(b), by Fig. 9 It can be seen that: when the nanogold particles are in the middle, the rise time is 17μs and the fall time is 106μs; when the nanogold particles are close to the top of the polymer core layer, the rise time is 35μs and the fall time is 117μs; this shows that the response speed of the nanogold particles is faster when they are in the middle.

[0124] Test Example 2 Loss and Polymer Core Thickness

[0125] 1. Test Method

[0126] The power consumption of Example 2 was tested, and the thickness of the polymer was changed to 1-6 μm by referring to the preparation method of Example 2, and the loss change when the particle size of the gold nanoparticles was 2-15 nm was tested. The analysis method adopted was: finite element analysis method, and the software adopted was: COMSOL simulation software.

[0127] 2. Test results

[0128] Test results such as Fig.10 and Fig.11 As shown by Fig.10 It can be seen that when the polymer thickness increases, the light loss will decrease, and when the particle size of the nano-gold particles decreases, the light loss will also decrease. Fig.11 It can be seen that the final power consumption of the switch chip prepared by the method of Example 2 is 6.9mW. At a lower power consumption, the light control function is realized, which is much lower than the power consumption of similar chips in the prior art. Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the solution. Although the present invention is described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand and can modify or replace the technical solution of the present invention on the basis of understanding this solution without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A hybrid integrated MZ mode all-optical switch chip buried with nano-gold particles, characterized in that: The invention comprises a substrate layer (20), on which an MZI type waveguide (23) is arranged, and an upper cladding layer (26) covering the MZI type waveguide (23) and having a lower refractive index than the MZI type waveguide (23) is grown outside the MZI type waveguide (23); the MZI type waveguide (23) is a dual-channel input MZI type optical waveguide structure, a nano-gold particle burying layer (24) for phase modulation is arranged in the middle of the dual-channel input MZI type optical waveguide structure, and the nano-gold particle burying layer (24) is formed by nano-gold particles dispersed in a polymer; the hybrid integrated MZ type mode all-optical switch chip buried with nano-gold particles omits an electrode structure.

2. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 1, characterized in that: The dual-channel input MZI type optical waveguide structure comprises a first parallel input straight waveguide (1) and a second parallel input straight waveguide (2); the other ends of the first straight waveguide (1) and the second straight waveguide (2) are respectively connected to a first curved waveguide (3) and a second curved waveguide (4); the other ends of the first curved waveguide (3) and the second curved waveguide (4) are inwardly connected to a third straight waveguide (5); the other ends of the third straight waveguide (5) are respectively connected to a third curved waveguide (6) and a fourth curved waveguide (7) outwardly; the other ends of the third curved waveguide (6) and the fourth curved waveguide (7) are respectively connected to a first curved waveguide (3) and a second curved waveguide (4) A coupling arm waveguide (8) and a second coupling arm waveguide (9), wherein the other ends of the first coupling arm waveguide (8) and the second coupling arm waveguide (9) are respectively connected to a fifth curved waveguide (10) and a sixth curved waveguide (11), the other ends of the fifth curved waveguide (10) and the sixth curved waveguide (11) are inwardly connected to a fourth output straight waveguide (12), the first input straight waveguide (1) and the second input straight waveguide (2) are parallel, and the first coupling arm waveguide (8) and the second coupling arm waveguide (9) are parallel; and the nano-gold particle buried layer (24) is arranged in the middle of the first coupling arm waveguide (8).

3. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 1 or 2, characterized in that: The nano-gold particles in the nano-gold particle embedding layer (24) have a light excitation wavelength of 0.45 to 0.65 μm, a particle radius of 10 to 80 nm, a particle spacing of 0.5 to 3.5 μm, and a particle doping concentration of 0.0025% to 0.5%.

4. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 1, characterized in that: The MZI type waveguide (23) comprises a first polymer core layer (27) and a second polymer core layer (25), wherein the materials of the first polymer core layer (27) and the second polymer core layer (25) are selected from EPO Core, SU-8 2002 or SU-8 2005.

5. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 1, characterized in that: The material of the upper cladding layer (26) is selected from polymethyl methacrylate, EPO Clad, polyester or polyimide.

6. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 1 or 2, characterized in that: The nano-gold particle embedding layer (24) is formed by dispersing nano-gold particles in a polymer, and the polymer is selected from polymethyl methacrylate, EPO Core, SU-8 2002 or SU-8 2005.

7. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 4, characterized in that: The thickness of the substrate layer (20) is 0.5 to 1 mm, the thickness of the first polymer core layer (27) is 1 to 10 μm, the thickness of the nano-gold particle burying layer (24) is 0.1 to 2 μm, the thickness of the second polymer core layer (25) is 1 to 10 μm, and the thickness of the upper cladding layer (26) is 2 to 15 μm.

8. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 2, characterized in that: The first curved waveguide (3), the second curved waveguide (4), the third curved waveguide (6), the fourth curved waveguide (7), the fifth curved waveguide (10) and the sixth curved waveguide (11) are S-curved waveguides with the same structure and size, and the S-curved waveguides use cosine-type function waveguides: , where x is the coordinate of the light transmission direction in the waveguide, y is the coordinate of the direction perpendicular to the waveguide, a is the projection of the S-bend waveguide parallel to the light transmission direction in the waveguide top-down direction, and d is the projection of the S-bend waveguide perpendicular to the light transmission direction in the waveguide top-down direction.

9. The hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claim 8, characterized in that: The lengths l1, l2 and l6 of the first input straight waveguide (1), the second input straight waveguide (2) and the output straight waveguide (12) are 0.5 to 1.5 cm; the horizontal lengths a1, a2 and a3 of the first curved waveguide (3), the second curved waveguide (4), the third curved waveguide (6), the fourth curved waveguide (7), the fifth curved waveguide (10) and the sixth curved waveguide (11) are 0.1 to 1 cm; the vertical distances d1, d2, d3, d4, d5 and d6 of the first curved waveguide (3), the second curved waveguide (4), the third curved waveguide (6), the fourth curved waveguide (7), the fifth curved waveguide (10) and the sixth curved waveguide (11) are 0.5 to 50 μm; the length l3 of the third straight waveguide (5) connected to the first curved waveguide (3) and the second curved waveguide (4) is 0.2 to 1.5 cm, the lengths l4 and l5 of the first coupling arm waveguide (8) and the second coupling arm waveguide (9) are 0.5 to 1.5 cm, the length l7 of the nano-gold particle buried layer (24) is 0.2 to 1 cm, and the width w is 1 to 10 μm.

10. The method for preparing the hybrid integrated MZ mode all-optical switch chip embedded with nano-gold particles according to claims 1-9, characterized in that: The steps include: S1. Preparation of the first polymer core layer Spin coating a first layer of polymer material (271) on a clean and dry substrate layer (20) surface, then placing it on a hot plate for pre-heating, and after cooling, bringing a first MZI type photomask (100) into contact with the first layer of polymer material (271), and then performing ultraviolet exposure, post-baking, cooling and development, removing areas outside the first MZI type photomask (100), and then performing a hardening treatment to obtain a MZI type first polymer core layer (27) sample; S2. Preparation of gold nanoparticle buried layer The nano-gold powder is mixed into the polymer material and uniformly mixed to form a composite material, and then the composite material is spin-coated on the MZI type first polymer core layer (27) sample in step S1, and heated and fixed to obtain a sample containing a nano-gold particle buried layer (24); S3. Preparation of the Second Polymer Core Layer Spin coating the second layer of polymer material (251) on the surface of the sample containing the nano-gold particle embedding layer (24) in step S2, heating and pre-baking, cooling and using a UV photoresist mask and plate alignment technology to contact the second MZI type photoresist plate (200) matching the first polymer core layer (27) with the surface of the sample, and accurately copy the pattern on the second polymer core layer (25) on the first polymer core layer (27); then UV exposure, post-baking treatment, cooling and development, removing the area outside the second MZI type photoresist plate (200), and then hardening treatment to obtain an MZI type second polymer core layer (25) sample; S4. Preparation of optical waveguide upper cladding A spin coating process is adopted to spin-coat a polymer as the material of the upper cladding layer (26) on the MZI type second polymer core layer (25) sample, heat and solidify it, and cool it to obtain the upper cladding layer (26) structure, thereby obtaining a hybrid integrated MZ type mode all-optical switch chip buried with nano-gold particles.

Citation Information

Patent Citations

  • Silicon dioxide-polymer three-dimensional MZI waveguide thermo-optical switch and preparation method thereof

    CN111175898A

  • line reactor to protect rotating machines from overvoltage waves

    SU82005A1

  • Waveguide thermal optical switch based on long-period metal surface plasma and preparation method of waveguide thermal optical switch

    CN104297948A

  • Low-power-consumption ridge type waveguide thermo-optic switch based on buried graphene heating electrode and preparation method thereof

    CN109799626A